On Women and the Praxis of Interreligious Dialogue Through The Arts - Diane Butler (UNHI PRESS, 2019)
This paper seeks to bring to the foreground the praxis of interreligious and intercultural dialogue through the arts in the field of Interreligious Studies. In particular, it looks at the unfolding of collaborative artistic offerings made by women from diverse cultures and faiths of Indonesia from 2000 to 2015 at the local level during cultural events held in Bali to the international level of the Parliament of the World’s Religions and the United Nations World Interfaith Harmony Week. By doing so, it hopes to show how the arts can embody the centuries-old principle of bhinneka tunggal ika (unity in diversity) today to support interreligious and intercultural dialogue, understanding and cooperation for world peace.